Enhancing Pancasila Education Through the Merdeka Mengajar Platform: An Analysis of Its Impact on Teaching Quality in Secondary Schools - Rizky Ramadhani; Junaidi Indrawadi; Azwar Ananda; Isnarmi Moeis (STAI Hubbulwathan Duri, 2024)
The Merdeka Mengajar Platform (PMM) is designed to support Indonesia's Independent Curriculum, aimed at enhancing instructional quality by aligning with the needs of individual schools. Specifically, in Pancasila Education, PMM is expected to facilitate effective, high-quality learning. This qualitative study used a case study approach to examine PMM’s effectiveness in Pancasila Education (PKn) at SMP Negeri 51 Palembang. Data were collected through observations and interviews with three PKn teachers, focusing on the challenges they encounter and their strategies to integrate PMM into their teaching. Analysis followed the Miles and Huberman model, involving data collection, display, reduction, and conclusion drawing. Findings indicate that PMM aids PKn teachers in delivering high-quality instruction by providing accessible teaching materials and interactive learning media aligned with the Independent Curriculum. However, challenges persist, including limited teacher familiarity with PMM, inadequate devices and internet access, and difficulties in integrating PMM with classroom practices. Teachers employ various strategies to overcome these barriers, including self-directed learning and school-provided training sessions, which enhance their technological competence and understanding of PMM. Additionally, the platform’s resources are adaptable, allowing teachers to modify content to meet curriculum standards effectively. PMM has significant potential to improve teaching quality in PKn education, though its effectiveness is influenced by the availability of resources and teacher training. Enhanced support in these areas could maximize PMM’s impact in Indonesian schools.